The role of vocational education and training in the integration of refugees in Austria, Denmark and Germany - Joergensen, Christian Helms [Verfasser]; Hautz, Hannes [Verfasser]; Li, Junmin [Verfasser] (My University, 2022)
“Vocational education and training (VET) plays a crucial role in the social inclusion of refugees. The aim of this paper is to examine how the VET systems of Austria, Denmark and Germany responded to the arrival of young refugees since 2015. VET in these countries are all categorised as systems of collective skill formation. The article examines and juxtaposes the legal rights, the actual opportunities and the barriers to refugees’ participation in and completion of VET at upper secondary level in the three selected countries. The study is based on reviews of literature and an analysis of refugee policies in the three countries. The findings of the study are divided into six categories that structure the analysis: admission requirements, validation of prior learning, vocational guidance, language training, social support measures and access to apprenticeships. The analysis finds that both asylum seekers and recognised refugees have more opportunities in Germany than in the other two countries regarding the key categories. The findings show no major differences in the position of the social partners in the three countries in relation to refugees’ participation in VET, however the national governments reacted differently to the influx of refugees.“ (authors’ abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; I 2.2.1 Westeuropa; I 2.1 Deutschland; 370; Flüchtling; Berufsausbildung; Berufliche Integration; soziale Integration; Berufsbildungssystem; Ausländerrecht; Einwanderungspolitik; Internationaler Vergleich; Österreich; Dänemark; Bundesrepublik Deutschland